2020
DOI: 10.1159/000510963
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein-Lymphocyte Ratio Identifies Patients at Low Risk for Major Morbidity after Oesophagogastric Resection for Cancer

Abstract: <b><i>Introduction:</i></b> Complications following oesophagogastric surgery have significant implications for patient recovery. <b><i>Objective:</i></b> identify cost-effective biomarkers which can predict morbidity. <b><i>Methods:</i></b> Analysis of all upper gastrointestinal resections in Galway University Hospital from 2014 to 2018 was performed. The ability of C-reactive protein (CRP), neutrophil-lymphocyte ratio (NLR), and CRP-lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Platelet counts in peripheral blood are markedly increased in patients with active UC compared with inactive UC (45), but not correlated with the Ulcerative Colitis Colonoscopic Index of Severity, which has an excellent overall assessment of endoscopic severity (46). C-reactive protein-to-lymphocyte ratio (CLR) was originally developed as a novel index to predict the major morbidity after esophagogastric cancer resection (27). To our knowledge, only Con et al explored the role of CLR for assessing the dynamic response to infliximab salvage treatment and predicting the risk of subsequent colectomy in patients with UC (47).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Platelet counts in peripheral blood are markedly increased in patients with active UC compared with inactive UC (45), but not correlated with the Ulcerative Colitis Colonoscopic Index of Severity, which has an excellent overall assessment of endoscopic severity (46). C-reactive protein-to-lymphocyte ratio (CLR) was originally developed as a novel index to predict the major morbidity after esophagogastric cancer resection (27). To our knowledge, only Con et al explored the role of CLR for assessing the dynamic response to infliximab salvage treatment and predicting the risk of subsequent colectomy in patients with UC (47).…”
Section: Discussionmentioning
confidence: 99%
“…CAR was calculated as the CRP levels (mg/L) divided by the albumin levels (g/L) ( 26 ). CLR was calculated as the CRP levels (mg/L) divided by the lymphocyte counts (10 9 /L) ( 27 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoshinaga Okugawa MD et al 14 proposed that CLR can be used as an effective marker for perioperative and postoperative management of patients with colorectal cancer. A study of esophageal cancer showed that a high preoperative CLR was signi cantly associated with clinicopathological factors for disease development and CLR can be a more reliable biomarker of a poor outcome than other combinations of in ammation biomarkers 35 . Although our research believes that CLR is not a predictor of PFS, but the level of CLR at the end of radiotherapy is an independent predictor of the clinical response of ESCC patients, which further expands the scope of CLR application.…”
Section: Discussionmentioning
confidence: 99%
“…Okugawa et al 14 proposed that CLR can be used as an effective marker for perioperative and postoperative management of patients with colorectal cancer. A study of esophageal cancer showed that a high preoperative CLR was significantly associated with clinicopathological factors for disease development and CLR can be a more reliable biomarker of a poor outcome than other combinations of inflammation biomarkers 35 . Although our research believes that CLR is not a predictor of PFS, but the level of CLR at the end of radiotherapy is an independent predictor of the clinical response of ESCC patients, which further expands the scope of CLR application.…”
Section: Discussionmentioning
confidence: 99%